1990
DOI: 10.1111/j.1365-2672.1990.tb01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic property of pediocin AcH produced by Pediococcus acidilactici H

Abstract: Pediocin AcH, a bacteriocin of Pediococcus acidilactici H, inhibits the growth of several food spoilage and pathogenic bacteria. The antigenic property of partially purified pediocin AcH was tested by immunizing mice and a rabbit. Pediocin AcH was not immunogenic in these animals as determined by immunoblotting even after conjugation to bovine serum albumin. The non-immunogenic nature of pediocin AcH, its non-toxicity to laboratory animals and its hydrolysis by gastric proteolytic enzymes may be considered fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 14 publications
1
43
0
1
Order By: Relevance
“…Recent attempts to produce bacteriocin-specific antibodies have had varied results (1,3,4,12,17,18). The relatively low molecular mass (Ͻ5,000 Da) of many bacteriocins makes them poorly or nonimmunogenic (22); conjugation of small bacteriocins to carrier proteins can improve their immunogenicity.…”
mentioning
confidence: 99%
“…Recent attempts to produce bacteriocin-specific antibodies have had varied results (1,3,4,12,17,18). The relatively low molecular mass (Ͻ5,000 Da) of many bacteriocins makes them poorly or nonimmunogenic (22); conjugation of small bacteriocins to carrier proteins can improve their immunogenicity.…”
mentioning
confidence: 99%
“…Future approaches should consider the application of bacteriocins in combination with treatments enhancing their effectiveness in foods. The antimicrobial efficiency of a bacteriocin may also be enhanced or broadened by using it in combination with other bacteriocins or other compounds including surfactants, chelating agents or other metal completing compounds (Bennik et al,1997;Ennahar et al, 1998 andBhunia et al,1990),…”
Section: Bacteriocin As Bio-preservative In Foods Industrymentioning
confidence: 99%
“…Pimiricin, a surface active antimycotic compound has also been approved (Henning et al, 1986). Morover, pediocin PA-1AcH was injected into mice and rabbits, and immunoblotting showed that it was non-immunogenic in both animals (Bhunia et al, 1990). The Food Safety and Inspection Service (FSIS) of the U.S. Department of Agriculture (USDA) evaluate the safety and effectiveness of bacteriocins in commodity segments such as meat and poultry products.…”
Section: Toxicity and Safety Considerationsmentioning
confidence: 99%